The development of community mediation in Malaysia: lessons from Ireland - Abdul Hak, Nora; Ambaras Khan, Hanna (2014)
Malaysia is a multiethnic country, whose population is made up of Malays, Chinese, Indians and various indigenous ethnicities. She has fared relatively well peacewise, despite simmering interethnic tensions and disputes. The Malaysian government, through the Department of National Unity and Integration has decided in 2007 to introduce community mediation as a means of resolving community disputes, as this is well established in countries like Singapore, Australia, the UK, United States, amongst others. Ho Khek Hua (2009) addressed the challenges faced i.e., the limited number of trained mediators, the issues of providing mediation training to community leaders, the need for case studies and financial constraints. In Malaysia, there is no legal framework as yet developed for community mediation. Thus, this research intends to explore the need for establishing such a framework. Interviews have been carried out in Malaysia with the aim of gathering the descriptions and opinions of the practitioners of mediation such as, community leaders, mediators, trainers, members of resident associations and individuals with knowledge and experience in community disputes. The research in Ireland involves studying the structure, practice and development of the community mediation centres. Besides library research, interviews and discussions have been conducted with project managers, mediators and trainers with respect to current status, planning and development of community mediation. The findings should assist us in our effort to improve the current structure, practice, training and development of community mediation in Malaysia.